1993
DOI: 10.1111/j.1600-0714.1993.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of sugar assimilation characteristics and colony phenotypes in pathogenic and commensal oral candidal isolates

Abstract: A comparison of sugar assimilation patterns has been made using 72 oral candidal isolates recovered from diseased and non-diseased patients. Significant differences were demonstrated between isolates recovered from diseased versus healthy mouths. In addition, significant changes in colony phenotype (switch frequency and morphologic predominance) were found to relate to predictive data generated from carbon source utilization data. These results suggest that biochemical properties and colony phenotypic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Yeasts from the MP patients exhibited more colony morphologies than those from the healthy subjects. This agreed with the diversity of species and biotypes in these patients, and with the observations of Hellstein et al (21) who found significant differences in colony phenotype between isolates recovered from diseased and healthy mouths. These colony phenotype differences were related to carbon source utilization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yeasts from the MP patients exhibited more colony morphologies than those from the healthy subjects. This agreed with the diversity of species and biotypes in these patients, and with the observations of Hellstein et al (21) who found significant differences in colony phenotype between isolates recovered from diseased and healthy mouths. These colony phenotype differences were related to carbon source utilization.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was no obvious correlation between biotypes and clinical infections. The dissimilar distribution of the predominant biotypes between or within the diseased and healthy group agrees with the results of Hellstein et al (21), who demonstrated significant differences in sugar assimilation patterns of candidal isolates recovered from diseased and non-diseased patients, but disagrees with a number of studies showing similarity in distribution of biotypes regardless of their pathological sources (8,16,30).…”
Section: Discussionsupporting
confidence: 78%
“…The study was done because there is evidence suggesting that particular strains of C. albicans are associated with specific forms of oral candidosis [7,13]. Previously, biotype differences between C. albicans from CHC lesions and adjacent normal mucosa have been reported, as has variation between strains from speckled and homogeneous CHC lesions [7].…”
Section: Discussionmentioning
confidence: 99%
“…The API-20C is a standard method for yeast identification based on carbohydrate assimilation and has been used successfully in epidemiological studies [12][13][14].…”
Section: Discussionmentioning
confidence: 99%